BMX: A scoping review of the literature - Camilleri, D.; Williams, R.; Sallis, R. J. T.; Hyde, C. L.; Quach, J. (Journal of Human Sport & Exercise, 2025)
Background: Bicycle Motocross (BMX) has evolved to cater to different styles of riders, including Flatland, Street, Park, and Dirt. BMX culture is characterised by a unique framework of regulations, guidelines, and principles of which a subculture has a pronounced anti-establishment sentiment and embraced do-it-yourself (DIY) practices, contributing to its distinctive identity within the realm of sport. Formal organisations have emerged, leading to the legitimisation of BMX through events such as the Olympics.To the author`s knowledge, this is the first attempt to identify and synthesise all academic publications on BMX and describe the emergence of this research. Methods: After adopting the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRIMSA) guidelines 940 studies were identified in the initial search and post screening 87 studies were included. Data was extracted to determine, among other things, the year of publication, methodology adopted, type of BMX and/or BMXers studied, discipline of the study, and focus of inquiry. No date limiter was applied to the search strategy. Results: We identified 87 BMX-related articles for analysis, published between 1982 to 2022. The majority of these studies were conducted within the disciplines of biomechanics and physiology/sports science with a primary focus on performance-enhancing techniques within BMX racing. Most studies have emerged from the UK, with both males and females as their gender sample, using quantitative methodology. Conclusions: This scoping review identified several trends in the history of BMX research. It also identified important gaps and possible avenues for future research to contribute to academic knowledge in this growing field.